The Effect of Attitude in Mediating Environmental Knowledge towards the Purchase Intention of Green Cosmetic Product - Ni Wayan Arika Putri; Ni Made Wahyuni; Putu Ngurah Suyatna Yasa (Universitas Warmadewa, 2021)
The existence of public awareness of environmental preservation today, makes many companies, especially cosmetics, try to put forward the ecological aspects and raise environmental issues as one of their marketing strategies. This study aims to explain attitudes and environmental knowledge in determining the purchase intention of a green cosmetic product. This study uses a purposive sampling technique for determining samples. The samples used were 100 people, all consumers who had never bought green cosmetic products domiciled in Denpasar City. The data obtained were analyzed by descriptive analysis and PLS. The results found that environmental knowledge and attitudes had a positive and significant effect on purchase intentions. Furthermore, the attitude mediates a portion of environmental knowledge towards the purchase intention of a green cosmetic product. Therefore, it was expected the consumer who already have knowledge of the environment has the potential to become customers for green cosmetics producers. In addition, the companies need to increase the intention of potential consumers to switch to green cosmetics products by highlighting the added value of consumption of green products and further research can add construct alternatives that affect the purchase intention of green cosmetics products such as environmental awareness and increase references related to this study.